Kinerja Batu Kapur Terhadap Nilai Califonia Bearing Ratio (CBR) Lapis Pondasi Perkerasan Jalan - Suardi, Enita; Lusyana, Lusyana; Mukhlis, Mukhlis; Fauzan, Muhammad; Zain, Kamilia (Jurnal Ilmiah Rekayasa Sipil, 2023)
Flexible Pavement is one of the road pavement constructions. In order for the flexible pavement to have adequate carrying capacity and durability to carry the load acting on it, the pavement is made in layers. The top layer is called the surface layer and below it is an aggregate foundation layer which is placed on top of the compacted subgrade. The material used as an aggregate foundation layer usually consists of crushed stone. However, seeing the abundance of limestone in Bukit Karang Putih, Indarung is expected not only to be used cement manufacture, but can be used as a substitute for the aggregate foundation layer. This research was conducted on the aggregate foundation layer of class A and the aggregate foundation layer of class B. Variations of mixture with limestone substitution in the aggregate foundation layer of class A and class B aggregate are 0%, 10% and 20%. The tests carried out include abrasion, compaction and CBR. The lowest abrasion test results for grade A aggregate foundation layer is 30.69%, while for grade B aggregate foundation layer is 31.79%. The results of the CBR test for class A aggregate foundation layers obtained the highest value for 10% limestone substitution, which is 75%, as well as for class B aggregate foundation layers, the highest value for 10% limestone substitution was 61%. The results of the CBR test that meet the requirements are found in the class B aggregate foundation layer, which is at least 60%.